If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -38 = -1x + 4x + -5 Reorder the terms: -38 = -5 + -1x + 4x Combine like terms: -1x + 4x = 3x -38 = -5 + 3x Solving -38 = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -38 + -3x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 -38 + -3x = -5 + 0 -38 + -3x = -5 Add '38' to each side of the equation. -38 + 38 + -3x = -5 + 38 Combine like terms: -38 + 38 = 0 0 + -3x = -5 + 38 -3x = -5 + 38 Combine like terms: -5 + 38 = 33 -3x = 33 Divide each side by '-3'. x = -11 Simplifying x = -11
| 22x=44y | | 17y-12y=25 | | 3x-4-8x+12= | | 15-4X=-X | | 3(x-3)+5=4(x-2)-10 | | 5ab-6ab+a= | | 2senx-cosx=-4 | | P=20+6ln(2q+1) | | 13x+15=3x+215 | | B+280= | | I=IR | | 5x+5x+130=180 | | -12+5m+10m=-2m-10-m | | 4(3x+3)=14x+11-2x+1 | | (3a-5)(2a+3)=0 | | -8=x/4+3 | | 3y=5x-y | | 5x+10=-48-7x | | 5(-3x-7)=-4(4x+9) | | 6(x-1)-5=4x+2(-3+x) | | 55-(2c+3)=4c(c+6)+c | | 7y+9=30 | | 7x-5=5(x+11)+2x-10 | | -2(m+2)=-8 | | (4x^8+11x^6-7x^2+3)-(9x^8-5x^4+8x^2-4)=0 | | 0.009(x+200)+0.06x=63 | | f(x)=10xfor | | 9c-6c=-8+11 | | 5x+6x-40=100-9x | | 45-4x*5=80 | | 8x+48=9x | | 0.5x+0.7x=1.7 |